Strategi Pengembangan Usaha pada UMKM Aisyah Jus di Kabupaten Malang - Emilly Nur Hapsari; Nida Adenia Rahma; Agus Hermawan; Agung Winarno (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as a driver of the local economy through expanding job opportunities and improving people's living standards. However, operational challenges are still often encountered by MSME actors, especially in product development, marketing strategies, and the implementation of the digital financial system. This study aims to formulate and apply contextual business development strategies for Aisyah Jus MSMEs in Malang Regency. Through a qualitative approach based on case studies, the research team carried out an intensive mentoring program for three months. The intervention is focused on three main domains: (1) product innovation through the development of banner design and brand identity, (2) marketing expansion via integration with the Grabfood platform, and (3) financial modernization with the adoption of the QRIS system. The results of this assistance are expected not only to strengthen the competitiveness of Aisyah Jus MSMEs in the digital ecosystem, but also to be a strategic reference for the development of similar MSMEs in the culinary industry.